Faktor-Faktor yang Mempengaruhi Alokasi Belanja Modal pada Provinsi di Pulau Sumatera - Azzah Oktapania; Zulkifli Zulkifli; Siska Aprianti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study is intended to examine the effect of the Degree of Fiscal Decentralization, Regional Financial Dependence, PAD Effectiveness, and SiLPA Financing Level on Capital Expenditure Allocation in Provinces on the Island of Sumatra during the period 2019 to 2023 with the official website of the Supreme Audit Agency of the Republic of Indonesia which is the main source of secondary data collection in this study. and multiple regression methods with Eviews 13. Based on the results of partial analysis, the variables of the degree of fiscal decentralization and regional financial dependence have a significant positive effect on the allocation of expenditure in the Province on the Island of Sumatra. In contrast, the variable effectiveness of PAD and the level of SiLPA financing on the allocation of capital expenditure in the Province on the Island of Sumatra. Simultaneous test results indicate that the four variables affect the allocation of capital expenditure. This finding indicates that an increase in the effectiveness of PAD and the level of SiLPA financing does not always lead to an increase in the allocation of capital expenditure if the provincial government on the island of Sumatra cannot manage the APBD budget properly.